Alternatif Pembelajaran Menulis Cerpen dengan Media Storyboard - Elsara Khairun Nisa; Fitriana Kartika Sari; M. Erwin Dwi Listyanto (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2023)
Writing skill is one of the difficult skills for students, especially in learning to write short story texts. The teacher's obstacle in learning to write short story texts is the less optimal use of learning media. Storyboard media is present as an alternative to overcome the problems that exist in learning to write short story texts which is the goal of this research. This study uses a qualitative approach with a descriptive design. The method used is a case study method with interview techniques. Storyboard media is suitable for learning to write short stories because in this media the emphasis is on elaboration, prediction or estimation, generating ideas, and sequencing. The storyboard media begins by making several illustrative images, which are then developed into a paragraph so that it becomes a complete story in a short story.